Java - Garside, Roger
Java: First Contact has been written from the ground up providing students with no programming background an introduction to object-oriented programming using the Java language. The authors introduce the use of pre-existing objects right from the start, laying the groundwork for successfully learning all major Java objects. This includes learning how to write objects, understanding the importance of inheritance, and object-oriented design. As a result, students establish a strong foundation in the object model so they can build an object-oriented system from start to finish. The book covers all major aspects of the Java language, including making use of classes from the Java standard library. In cases where standard classes are too complex, author defined classes are available. Later chapters are dedicated to covering advanced aspects of the Java language, including GUI's, applets, input/output, and elementary data structures, enabling students to use a wide variety of tools when writing Java programs